Founder effects facilitate the use of a genotyping‐based approach to molecular diagnosis in Swedish patients with familial hypercholesterolaemia. (6th May 2021) - Benedek, P.; Jiao, H.; Duvefelt, K.; Skoog, T.; Linde, M.; Kiviluoma, P.; Kere, J.; Eriksson, M.; Angelin, B.
Abstract: Aim: To investigate whether genotyping could be used as a cost‐effective screening step, preceding next‐generation sequencing (NGS), in molecular diagnosis of familial hypercholesterolaemia (FH) in Swedish patients. Methods and results: Three hundred patients of Swedish origin with clinical suspicion of heterozygous FH were analysed using a specific array genotyping panel embedding 112 FH‐causing mutations in the LDLR, APOB and PCSK9 genes. The mutations had been selected from previous reports on FH patients in Scandinavia and Finland. Mutation‐negative cases were further analysed by NGS. In 181 patients with probable or definite FH using the Dutch lipid clinics network (DLCN) criteria (score ≥ 6), a causative mutation was identified in 116 (64%). Of these, 94 (81%) were detected by genotyping. Ten mutations accounted for more than 50% of the positive cases, with APOB c.10580G>A being the most common. Mutations in LDLR predominated, with (c.2311+1_2312‐1)(2514)del (FH Helsinki) and c.259T>G having the highest frequency. Two novel LDLR mutations were identified. In patients with DLCN score < 6, mutation detection rate was significantly higher at younger age. Conclusion: A limited number of mutations explain a major fraction of FH cases in Sweden. Combination of selective genotyping and NGS facilitates the clinical challenge of cost‐effective genetic screening in suspected FH. The frequency of APOB c.10580G>A was higher than previously reported in Sweden. The lack of demonstrable mutations in the LDLR, APOB and PCSK9 genes in 1/3 of patients with probable FH strongly suggests that additional genetic mechanisms are to be found in phenotypic FH. Abstract :